2004
DOI: 10.1017/s0016756804008908
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Timan–Pechora and South Barents Sea basins

Abstract: We have analysed 129 stratigraphic sections from the Timan-Pechora basin, from its adjacent continental shelf and from the South Barents Sea basin, in order to determine whether existing models of extensional sedimentary basin formation can be applied to these intracratonic basins or whether new mechanisms of formation need to be invoked. The subsidence history of each section has been calculated using standard backstripping techniques. An inverse model, based on finite-duration lithospheric stretching, has th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 23 publications
0
50
0
Order By: Relevance
“…Multiple phases of extension and rifting have been recognised in the southern Barents Sea from the Carboniferous, in Permo-Triassic time and also in the Late Jurassic-Early Cretaceous, with Late Cretaceous-Early Tertiary basin inversion (O'Leary et al, 2004;Shipilov, 2015). The northward-dipping wedge of Palaeozoic to Triassic sedimentary rocks in the Kola-Kanin Monocline off the Murmansk Coast reaches a total thickness of 5 km (Fig.…”
Section: 'K' -Devonian Lavas 'L' -Phanerozoic Dykes 'M' -Phoscoritementioning
confidence: 95%
See 2 more Smart Citations
“…Multiple phases of extension and rifting have been recognised in the southern Barents Sea from the Carboniferous, in Permo-Triassic time and also in the Late Jurassic-Early Cretaceous, with Late Cretaceous-Early Tertiary basin inversion (O'Leary et al, 2004;Shipilov, 2015). The northward-dipping wedge of Palaeozoic to Triassic sedimentary rocks in the Kola-Kanin Monocline off the Murmansk Coast reaches a total thickness of 5 km (Fig.…”
Section: 'K' -Devonian Lavas 'L' -Phanerozoic Dykes 'M' -Phoscoritementioning
confidence: 95%
“…1), thick, very coarse-grained, sandstone turbidites are interbedded with conglomerates and a basal olistostrome-breccia (Siedlecka et al, 1995b;Mitrofanov et al, 2004). In the eastern Kola Peninsula, the Riphean sedimentary rocks are much finer grained, with thick siltstone units (Baluev et al, 2009), and were originally deposited in half-grabens within mountainous terrain (O'Leary et al, 2004). Along the north coast of the Kola Peninsula, Riphean rocks have been faulted and laterally displaced along the Karpinsky Lineament ( Fig.…”
Section: Neoproterozoic Sedimentary Rocksmentioning
confidence: 99%
See 1 more Smart Citation
“…1, 2). Several published studies discuss the nature of the observed rapid subsidence in the East Barents Sea basin since there are no major extensional faults and thus a classical rift scenario is unlikely (Aplonov et al, 1996;Gac et al, 2012Gac et al, , 2013Ivanova et al, 2011;Johansen, 1992;O'Leary et al, 2004;Petrov et al, 2008;Semprich et al, 2010). Oldest sediments of the South Kara Sea basin are assumed to have accumulated in response to rifting in the Late Permian to Middle Triassic followed by a post-rift thermal subsidence phase lasting until Cenozoic times (Nikishin et al, 2011).…”
Section: Geological Settingmentioning
confidence: 99%
“…The Lower Palaeozoic Baltica Palaeoplate (Cocks & Torsvik 2005) comprises the East European Craton as its core with three major crustal segments Fennoscandia, Sarmatia and Volgo-Uralia that collided between ca 2.0 and 1.7 Ga (Bogdanova et al 2008), and the Pechora Basin that became accreted to Baltica in the late Vendian as a part of the Timanide Orogeny (Bogolepova & Gee 2004, O'Leary et al 2004. The Kara block has been interpreted as a part of Baltica ( Fig.…”
Section: Geological Settingmentioning
confidence: 99%